Effect of Breadfruit Leaf (Artocarpus altilis) Extract on Histological Features of the Seminiferous Tubules in Diabetic Wistar Rats - Wulandari, Puspa; NurCita, Boenga; Kristanti, Melly; Irsyad, Nasihin Saud (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Hyperglycemia can lead to increased free radicals formation that can potentially cause oxidative stress as a trigger for male reproductive organ damage, damaging the histological structure of seminiferous tubules as a place for sperm cell formation. Flavonoids in breadfruit (Artocarpus altilis) are known to be able to counteract free radicals caused by diabetes. The research was conducted to observe the effect of breadfruit leaf extract on the histological features of seminiferous tubules in diabetic Wistar rats. This true-experimental research with post-test-only control group design and purposive sampling technique to obtain 30 Wistar white male rats 8-12 weeks old weighing 150-200 g were grouped into 5 groups. The negative control group was fed standard food; the positive control was induced with STZ, and treatments 1, 2, and 3 were given the extract at doses of 200 mg/kgBW, 400 mg/kgBW, and 800 mg/kgBW consecutively for 30 days. Assessment of spermatogenesis in the histology of seminiferous tubule using Johnsen score criteria. Data were analyzed by the Kruskal-Wallis and the Mann-Whitney U posthoc test, which revealed significance with a p-value of <0.001 (<0.05). This study showed that breadfruit leaf extract can improve the histology of seminiferous tubules. Despite not being as good as the histology of seminiferous tubules under normal conditions, it has a therapeutic effect.